Children on Strike. the Case of National Glass Factory. Chile, 1925 [Niños en Huelga. el Caso de la Fábrica Nacional de Vidrios. Chile, 1925 - Rojas-Flores, J (Universidad de Antioquia, 2016)
This article attempts to understand the origin and the manner of child participation in the strike movements in the early 20th century, particularly in a conflict developed in 1925. Unlike other contemporary cases, children workers of the National Glass Factory played a central role in raising their own demands. Based on newspapers and archival documentation, this research manages to reconstruct this unique social experience, exploring the factors that help explain it, including the existence of particular forms of sociability within the factory.